Dietary intake and growth of HIV exposed and unexposed 6–12 months old infants in South Africa - Phumudzo Tshiambara; Marinel Hoffman; Heather Legodi; Yusentha Balakrishna; Ute Feucht (Maternal and Child Nutrition)
Abstract Factors affecting the growth of HIV‐exposed‐uninfected (HEU) children are multi‐factorial, with limited information available on the dietary intake from 6 months. This study compared the dietary intake, micronutrient composition of breastmilk, and growth of HEU and HIV‐unexposed‐uninfected (HUU) infants aged 6 and 12 months in an urban setting. A repeated cross‐sectional study used structured questionnaires to collect socio‐demographic, dietary intake, food group data, and anthropometric measurements in the Siyakhula study. The HEU (48%) and HUU (52%) infants were included (total n = 181). At 6 months, HEU infants had lower weight‐for‐age z‐scores (WAZ) (−0.6 ± 1.1 vs. 0.1 ± 1.2; p < 0.001), length‐for‐age z‐scores (−0.8 ± 1.4 vs. −0.1 ± 1.2; p < 0.001), and mid‐upper‐arm circumference‐for‐age z‐scores (MUACAZ) (0.5 ± 1.1 vs. 1.0 ± 0.9; p < 0.001) than HUU infants. At 12 months, HEU infants had lower WAZ, MUACAZ, and weight‐for‐length z‐scores compared to HUU infants (p < 0.05). Stunting was found at 6 (15%) and 12 (12%) months in HEU infants. The micronutrient composition of breastmilk fed to both groups was similar. Breastfeeding rates were lower in HEU than in HUU infants at 6 (49% vs. 64%; p = 0.005) and 12 (24% vs. 46%; p = 0.002) months. Less than 3% of HEU and HUU infants achieved minimal dietary diversity scores at 12 months. Dietary intake of fat was similar in all breastfed infants, but iron and vitamin B12 were higher in non‐breastfed HEU infants at 12 months. HEU infants had lower breastfeeding rates than HUU infants. A lack of dietary diversity was found in all infants. Nutrition education and counselling in the complementary feeding phase are essential for optimal growth.